Ain't nobody's fool [large type] : the life and times of Dolly Parton - Ackmann, Martha (Thorndike Press large print top shelf., 2026)
"From her impoverished childhood in the Smoky Mountains to international stardom, Dolly Parton has exceeded everyone's expectations but her own. The day after her high school graduation, she boarded a bus for Nashville, but record executives turned her down. When Dolly finally got her foot in the door, her talent and focus catapulted her to the top of country charts, the pop world, and movie stardom. Shunned by many in Nashville who saw her ambition as a betrayal of her country music roots, Dolly became the target of death threats, lawsuits, and a judge who threatened to throw her in jail, but she came back stronger than ever."--